Quranic Ethics Toward People with Disabilities: Exploring the Narratives of Classical to Contemporary Commentaries on QS. ‘Abasa/80:1-4 (ADDIN, 2025)
Across cultures, people with disabilities often challenge negative attitudes, discrimination, and even social exclusion. At the same time, religious narratives (al-Qur’ān) are frequently understood to justify the difference between people with disabilities (a’mā) and ordinary people (al-baṣīr). Therefore, this paper will critically study the interpretation of QS. ‘Abasa 1-4 to redefine Quranic ethics in dealing with people with disabilities. This paper analyzes the interpretation of Muslim scholars from classical to contemporary on QS. ‘Abasa 1-4 through an analytic descriptive approach. This paper suggests the orthodoxy of classical to modern interpretations in comprehending QS. ‘Abasa 1-4. Three main topics, in general, are highlighted by classical to contemporary exegetes in understanding QS. ‘Abasa 1-4. Firstly, the profile of ‘Abdullāh ibn Ummī Maktūm as a person with disabilities who visited the forum of the Prophet Muhammad. Although there are different opinions, most commentators believe ‘Abdullāh ibn Ummī Maktūm is the figure discussed in  QS. ‘Abasa 1-4. Secondly, ‘Abdullāh ibn Ummī Maktūm’s visit was to seek religious education from the Prophet Muhammad. This indicates that the Quran prioritizes equal rights to education, regardless of wealth, strength, disability status, etc. Thirdly, the Prophet Muhammad’s reaction of frowning and turning away served as a form of moral education and teaching etiquette in public spaces to anyone, regardless of social status.